Foto seleção de mielomas e hibridomas murinos na produção de anticorpos monoclonais - Mion, Woner [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The production of monoclonal antibodies (mAbs) for medicine is highly important, being considered the greatest innovation of the biotechnologic industry over the years. The method described by Köhler e Milstein demands cellular selection through biochemistry ways using HAT (culture medium with hypoxanthine, aminopterin and tymidhine). By the increasing use of lights in the medical areas, this paper searches to evaluate the application of LED (Light Emitting Diode) - wave length of 475nm - in the selection of cells involved on monoclonal antibodies production, in order to offer a new option for hybridoma selection. Cell culture of Murine Myeloma (NS1) and MRSA 3-75 and 4-27 in complete culture medium with 10% of fetal bovine serum (FBS) were separated in six groups for each cellular type (12 samples), being: G1: control group (not irradiated), G2: 1 J/cm2; G3: 3 J/cm2; G4: 5 J/cm2; G5: 10 J/cm2; G6: 20 J/cm2. To determine the behavior of cells, the following tests were made: viability tests by Flow Cytometry and MTT (3-(4,5-dimethyl thiazol-2-yl)-2,5-diphenyl tetrazolium bromide), ELISA and Emission Spectrometry to check hydridomas’ secretory profile and Tripan blue stain to determine cellular growth rate. The results show that there were bioinstimualtion of NS1 and MRSA 3-75 and 4-27 in doses above of 5 J/cm2, which promoted the increase of death by necrosis and late apoptosis with the reduction of monoclonal antibodies production (hybridoma) in all experimental groups. The MRSA 4-27 hybridomas presented biostimulation as for the anitbodies production in 31% at the dose of 1 J/cm2, although the MRSA 3-75 didn’t present any alteration of secretory profile. The LED with wave length of 475nm didn’t promoted photoselection of hybridomas and myelomas after the exposure to light. However, it biostimulated the cellular growth (NS1) and the increased the secretion of immunoglobulins (MRSA 4-27), which is the main interest of ...

A produção de anticorpos monoclonais (mAbs) é de extrema importância na área médica, sendo considerada a grande inovação da indústria biotecnológica. O método descrito por Köhler e Milstein exige a seleção celular por vias bioquímicas através do meio HAT (meio com hipoxantina, aminopterina e timidina). Com o crescente emprego da luz na área médica este trabalho buscou avaliar o emprego do LED (abreviação de Light Emitting Diode) com comprimento de onda de 475nm na seleção das células envolvidas na produção de anticorpos monoclonais com vistas a oferecer uma nova opção na seleção de hibridomas. Culturas celulares de Mieloma Murino (NS1) e MRSA 3-75 e 4-27 em meio completo 10% SFB foram segregadas em seis grupos para cada tipo celular (12 amostras), sendo: G1: controle (não irradiado); G2: 1 J/cm2; G3: 3 J/cm2; G4: 5 J/cm2; G5: 10 J/cm2; G6: 20 J/cm2. Com vistas a determinar o comportamento das células frente ao efeito da luz, foram avaliadas a taxas de viabilidades das células por Citometria de fluxo e MTT (3-(4,5-dimethyl thiazol-2-yl)-2,5-diphenyl tetrazolium bromide), perfil secretor dos hibridomas por ELISA e nanodrop e taxa crescimento celular pela coloração de Azul de Tripan. Os resultados mostraram que houve bioinibição de NS1 e MRSA 3-75 e 4-27 em doses superiores a 5 J/cm2 promoveram aumento da morte por necrose e apoptose tardia com supressão da produção de anticorpos (hibridomas) em todos os grupos experimentais. Os Hibridomas MRSA 4-27 apresentaram bioestimulação quanto a produção de anticorpos em 31% na dose de 1 J/cm2 porém, o MRSA 3-75 não apresentou alteração no perfil secretor. O LED no comprimento de onda de 475nm não promoveu fotoseleção de mielomas e hibridomas após exposição à luz. Mas, bioestimulou o crescimento celular (NS1) e promoveu aumento da secreção de imunoglobulinas (MRSA 4-27), principal interesse dos laboratórios de bioengenharia que utilizam esta tecnologia
Keywords: Fotoquimioterapia; Anticorpos monoclonais; Luz - Efeito fisiologico; Citometria de fluxo; Light Physiological effect